Implementation the Professionalism Value in Shaping the Personality of Islamic Education Teachers - Ahmad, Aliza Che; Che Noh, Mohd Aderi; Muhamad, Norhisham; Ikhwan, Afiful (Tahta Media Group, 2023)
Teaching is essential in forming balanced individuals in line with the desires and needs of Malaysia's national education policy in producing qualified and qualified teachers. Practising the value of teaching professionalism is an effort to form teachers with superior personalities and global insight. This research aims to explain Islamic education teachers' understanding of professionalism values and explore the practical application of Islamic education teachers' professionalism values. This type of research is qualitative with a case study design, obtaining data through interviews and observation. The discussion results show that the need to practice professional values in teaching is an essential aspect of forming the teacher's personality to develop professionalism. Overall, the research findings show two main themes found in the practice of professional values in teaching: (a) value practices in the personal realm and (b) value practices in the professional realm. The research results found that Islamic religious education teachers understand the concept of practical values of teaching professionalism and can apply practices born from these concepts in their personal and professional lives. The practice of professionalism values needs to be implemented by teachers so that they can be role models in ensuring quality educators and producing quality people. The implications of the findings of this research can be used as guidance for all parties, especially policymakers, namely the Ministry of Education, in ensuring that the value aspect becomes the main focus in the recruitment and training process that will be carried out by the conditions and criteria that have been determined to ensure that the teacher appointment process is realized smoothly. Full of dedication and excellence, in line with the desire to produce world-class Human Resources (HR).